The impact of trust, security, and privacy on individual's use of the internet for online shopping and social media: a multi-cultural study. (23rd May 2019) - Alshare, Khaled A.; Moqbel, Murad; Al-Garni, Mohammad A.
This paper examines through the lens of expectancy-valence theory the impact of trust, privacy, and security on the decision to use the internet for online shopping and social media. It also investigates the moderating impact of Hofstede's cultural dimensions on the hypothesised relationships. The comparative analysis of 302 surveys from users in the USA and Qatar revealed that trust in internet technology and trust in vendors are the strongest two factors in making decisions to use the internet for online shopping and social media. The results indicated that the cultural dimensions moderated the hypothesised relationships. Surprisingly, Qataris respondents, compared to US respondents, were more influenced by privacy concerns when making decisions to use the internet for online shopping or social media. Implications for researchers and practitioners are reported.